Determines the application of smart tourism as an electronic commerce application in the form of B2C) to attract tourists to Saudi Arabia - فايد عبير السيد (Journal of Economics and Administrative Sciences, 2019)
Abstract: The study focused on the application of smart tourism as one of the applications of electronic commerce in the form of (B2C) to attract tourists to Saudi Arabia, where the tourism sector is one of the important sectors on which the Kingdom depends on the diversity of its economy. The purpose of the research: With the issuance of tourist visas for the first time the study noted a deterioration in the case of Saudi tourist sites over the Internet, which do not live up to this great interest by the Saudi government for this sector, which became vital to them. The study tried to identify the reality of the Saudi tourist sites through the Internet in order to identify the suitability to attract tourists through the Internet, as well as to identify the determinants of the application of e-tourism these sites so as to be able to attract tourists and then to the tourist destinations marketed through these sites. Methodology: The study was based on the distribution of an electronic questionnaire on the sample of the study. The aim of the study was to collect the data and geographical diversity of the sample items either inside or outside Saudi Arabia. The responses by vocabulary in Arab countries and these countries are targeted to the tourist attraction of the Kingdom as they can be persuaded and attracted to the destinations of Saudi Arabia at the start of the launch of Saudi tourism. The research used the Lycert five-dimensional scale to measure the views of the sample of the sample towards the variables of the study, which consists of 5 degrees, and was based on some statistical analysis included in the SPSS program to measure the validity of error of the study hypotheses. Research Limitations: The search was limited to the determinants of the Smart Tourism application over the Internet. These limitations were limited to cloud computing, mobile communications activation, the things Internet and Artificial intelligence. The study also excluded religious tourism and focused on other types of tourism except religious tourism. Findings: The results of the research found that the reality of the Saudi tourist sites through the Internet does not apply in any form of smart tourism, but it could not attract any tourists, and it turned out that smart tourism is more than just e-tourism is beyond that and has determinants to apply cloud computing, mobile communications activation, The things Internet and Artificial intelligence. The originality and scientific value of the research: The research sought to identify the reality of the tourist sites in the Saudi market and then to determine the extent of their application to smart tourism or not. The research found a lack of previous studies in this subject as it did not address any study of Saudi tourism (other than religious tourism excluded from the current study) Saudi Tourism Websites. There is also no Arab study at all on the subject of smart tourism, and foreign studies have been addressed to smart tourism in a manner of major shortcomings as most of them dealt with the concept of tourism and other intelligent studies dealt with a single requirement of smart tourism and did not deal with the studies in an integrated manner The shortcomings of the present study are dealt with. .